How to characterize and influence the customer journey: The case of the purchase of counterfeit luxury products - Castilho, Tatiana Soares (2021)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Marketing Research and CRM